SpiderNet: an integrated peer-to-peer service composition framework - Xiaohui Gu; Nahrstedt, K.; Bin Yu (Proceedings of the IEEE International Symposium on High Performance Distributed Computing, 2004)
Service composition is highly desirable in peer-to-peer (P2P) systems where application services are naturally dispersed on distributed peers. However, it is challenging to provide high quality and failure resilient service composition in P2P systems due to the decentralization requirement and dynamic peer arrivals/departures. We present an integrated P2P service composition framework called SpiderNet to address the challenges. At service setup phase, SpiderNet performs a novel bounded composition probing protocol to provide scalable quality-aware and resource-efficient sendee composition in a fully distributed fashion. Moreover, SpiderNet supports directed acyclic graph composition topologies and explores exchangeable composition orders for enhanced service quality. During service runtime, SpiderNet provides proactive failure recovery to overcome dynamic changes (e.g., peer departures) in P2P systems. The proactive failure recovery scheme maintains a small number of dynamically selected backup compositions to achieve quick failure recovery for soft realtime streaming applications. We have implemented a prototype of SpiderNet and conducted extensive experiments using both large-scale simulations and wide-area network testbed. Experimental results show the feasibility and efficiency of the SpiderNet service composition solution for P2P systems.